ADAPTATION STRATEGIES OF MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMES) IN FACING DIGITAL ECONOMY DYNAMICS: A QUALITATIVE STUDY IN THE ERA OF TECHNOLOGICAL TRANSFORMATION - Rasid, Farhan; Wijaya, Cahyadi; Jayanti, Marlina (Institut Teknologi Bisnis dan Kesehatan Bhakti Putra Bangsa Indonesia, 2026)
The massive technological transformation that has taken place in the last two decades has driven significant changes in the structure and mechanisms of the global and national economies. The development of the internet, digital platforms, and electronic payment systems has created a digital economy ecosystem that changes people's production, distribution, and consumption patterns. In this context, Micro, Small, and Medium Enterprises (MSMEs) are faced with new challenges as well as opportunities. This research aims to analyze in depth the adaptation strategies carried out by MSME actors in dealing with the dynamics of the digital economy in the era of technological transformation. This research uses a qualitative approach with a phenomenological study design to explore experiences, perceptions, and concrete strategies applied by MSME actors in the process of digitizing their businesses. Data was obtained through in-depth interviews, field observations, and documentation of MSME actors who have utilized digital platforms in their business activities. Data analysis is carried out through the stages of data reduction, categorization, data presentation, and inductive conclusion drawn. The results of the study show that the adaptation strategy of MSMEs includes the transformation of digital-based marketing models, increasing technological literacy, utilizing social media and marketplaces, strengthening collaboration networks, and adjusting financial management through digital payment systems. However, the adaptation process still faces obstacles in the form of limited human resources, lack of access to technology training, and fierce competition in the digital space. This study concludes that the success of MSME adaptation in the digital economy is highly determined by the ability to innovate, continuous learning, and support for an inclusive and sustainable policy ecosystem.